Pathogenesis and Transmission of Classical and Atypical BSE in Cattle - Costassa, Elena Vallino (Food Saf (Tokyo), 2016)
Many mammalian species can be affected by prion diseases, also known as transmissible spongiform encephalopathies (TSEs). “Classical” bovine spongiform encephalopathy (C-BSE) was the first prion disease recognized in cattle and it is the only known zoonotic prion disease, having caused variant Creutzfeldt-Jakob disease (vCJD) in humans. Based on the biochemical signatures of disease-associated prion protein (PrP(Sc)), two distinct forms of atypical bovine spongiform encephalopathies (H-BSE and L-BSE) have been distinguished from C-BSE since 2004. To date there is no comprehensive information about the origin of atypical BSEs (sporadic vs. acquired) and this has an influence on the interpretation of the knowledge gathered from experimental studies, regarding how well such models may represent the real distribution of the agent in the body of naturally affected animals. Moreover, there are only very limited data available concerning the pathogenesis of both atypical BSE forms, as compared to C-BSE. Thus, precautions that are presently taken to minimize the risk of prion contamination of the food supply might not be as effective at preventing the spread of these recently recognized strains. In the last few years a wide range of experimental transmission studies of atypical strains in different animal hosts have been performed. The most recent data on classical and atypical BSE studies concerning characteristics, pathogenesis and transmissions in cattle will be summarized in this review.